Pengaruh Stres Tekanan Ketaatan Terhadap Pencegahan Kecurangan Akuntansi - Putri, Julieta Amartya; Ismatullah, Ismet; Sudarma, Ade (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
The aim of this study determines the influence of stress obedience pressure on accounting fraud prevention. The variables used in research are stress obedience pressure and accounting fraud prevention. The data used is the primary data collected through questionnaires dissemination. Research samples were obtained by 36 people who work on BJB bank of Sukabumi branch with nonprobability sampling methods and saturated sampling technique. Data analysis method used the Structure of the SEM-PLS with WarpPLS Program 5.0. Based on research results : (1) Stress Obedience Pressure affect to Accounting Fraud Prevention, indicated by β = -0,485 and significant value of 0,001. (2) Based on the hypothetical test it shows that Stress Obedience Pressure affect to Accounting Fraud Prevention by 23% the remaining 77% is affected by other unstudied factors in this research.